Dakwah di Era Digital - Budiantoro, Wahyu (Fakultas Dakwah IAIN Purwokerto, 2017)
These days dakwah is not only interpreted as transformation of a pure religious value, but also transformation of a more relevant value including many aspects in digital era. Digital era is when society succumbed into the flow of information causing cultural shock and difficulties on synthesizing meaning from those scattered information. Dakwah on Digital age must accommodate societal needs which tend to move into a mass society. It results in strategy and more humane and innovative dakwah methods. One of innovative dakwah methods is conducted dakwah activities through digital media,with the consequences of this is that da’i must developed soft skill and technological capabilities. Another beneficial comes from this is that dakwah could become more modern and practical in terms of methods and material. On the other hand, citizen Journalism as a mass cultural product and the results of technological development, gives an opportunity for da’i to able to record the entire activities, including the dynamics of islamic life. In terms of learning curriculum, dakwah in digital format must be included, so then the intellectual and cultural spirit which flourished in pesantren could be adapted and competed in a global world.